ANALISIS RAJUNGAN (Portunus pelagicus), KOMPOSISI BYCATCH DAN ALAT TANGKAP JARING DARI TANGKAPAN NELAYAN DI PERAIRAN KABUPATEN ASAHAN SUMATERA UTARA - Friyuanita Lubis; Agusriati Muliyana; Mira Mauliza Rahmi; Hilham Mulia Rizki (Journal of Aceh Aquatic Sciences, 2021)
The resources of blue swimming crab (BSC) (Portunus pelagicus) in Asahan Waters are caught by fishers, that have used gillnets, which is the main target and bycatch is used to meet benefit activities, then there are concerns about the inappropriate crab management. This study aims to determine a number of crab production, crab condition, main target and bycatch proportion and the crab fishing gear feasibility. The method used in this research is a descriptive survey method. The results showed that the catch of BSC was 434.25 kg (86%) as the main target and bycatch was 15 kg (14%) with a composition of 19 species. Total of BSC was 1081 with an average carapace width of 103.57 mm for males and 96.60 mm for females. Based on the Decree of Minister of Maritime Affairs and Fisheries No.1 year 2015, it is assumed that the gillnet used by fishers is a not feasible catching category for the juvenile crab growth.